Teaching sustainability in tourism education: a teaching simulation. Issue 5 (8th July 2020) - McGrath, G. Michael; Lockstone-Binney, Leonie; Ong, Faith; Wilson-Evered, Elisabeth; Blaer, Madelene; Whitelaw, Paul
Abstract: Addressing the dearth of sustainable tourism teaching simulations, this article details the design, development, testing and validation of a destination development game simulation designed to reinforce the teaching and learning of sustainable tourism principles. We discuss two stages of model development, including an earlier game developed using system dynamics and an evolved version with agent-based modelling extensions, incorporating a flock leadership framework and network theory, which together provided a framework for considering the human dynamics provoked within the simulation interaction. For Study 1, simulation validation was based on feedback received from staff and students of an Australian higher education institution for which students were assessed on their use of the simulation in a classroom setting. The simulation illustrated to the students the complexity of decision-making in tourism destinations, while highlighting the need for a broader range of stakeholder interactions. We detail the initial validation of Study 2 as a precursor to further testing. The development process has highlighted the importance of a coherent and familiar context as background to using such a simulation as a teaching and learning tool. Further validation will be conducted in diverse institutions to trial and observe different modes of uptake of the simulation.